Employees perceptions of non‐monetary recognition practice and turnover: Does recognition source alignment and contrast matter?. (7th May 2021) - Chênevert, Denis; Hill, Kevin; Kilroy, Steven
Abstract: Nonmonetary recognition originates from various sources (distal and proximal) and research has yet to examine the interplay among them. Results of a 2‐year time‐lagged study ( N  = 221), employing polynomial regression and response surface analysis, revealed that when distal organisational nonmonetary recognition is aligned with recognition from proximal sources, employees had lower turnover intentions and, indirectly, were less likely to quit 2 years later. For the most part, these relationships do not differ significantly based on the level at which alignment of distal and proximal recognition occurs. In terms of contrasts, when distal recognition exceeds the level of proximal recognition from the supervisor, turnover intentions are higher. For other proximal sources (co‐workers, physicians and patients), turnover intentions were higher irrespective of the type of contrast. This study adds to the strategic HRM literature by showing that contrasts between distal and proximal recognition undermine HR practice perception and employees' organisational attachment.